Redescription of spittlebugs, Cercopis vulnerata Rossi, 1807 (Hemiptera: Cercopidae) from Kurdistan Region– Iraq. - Shatha H. Ahmmed; Dilzar H. Mawlud; Nabeel A. Mawlood (Zanco Journal of Pure and Applied Sciences, 2023)
The present paper provides a comprehensive description of the spittlebugs, Cercopis vulnerata Rossi, 1807, in Kurdistan Region of Iraq. From April to the end of July of 2021, the specimens were taken from some flowers of herbaceous plants. Photographs have been taken of certain significant taxonomic components, include the mouthparts, antennae, fore wing, 8th abdominal segment and male genitalia. The locations of collection, date of collection and the hosts of plants have been recorded.